Noble sentiments and the rise of Russian novels : a European literary history - Hoogenboom, Hilde (Toronto ; Buffalo ; London : University of Toronto Press, 2025)
Noble Sentiments and the Rise of Russian Novels: A European Literary History is the first comprehensive study of the overwhelming influence of European bestsellers in translation on nineteenth-century Russian literature, and the first to examine women and men as nobles and equals in the creation of a new literature against substantial odds: 90% of novels in Russia through the 1850s were foreign. Together, they adapted the fundamental European conversation - on a sentimental moral education in duty to the greater good - to their search for a meaningful life of purpose as hereditary nobles, compelled to serve in the military and civil service in exchange for the right to own land with serfs. This new history of well-integrated Russian and European literary markets is evident in what everyone everywhere was reading. Using data from eighteenth- and nineteenth-century book and periodical catalogues in Russia, Germany, France, and Britain, Hoogenboom visualizes, in 14 tables and 22 graphs, readers' large appetite for translated sentimental and sentimental realist novels, many by such women as Madame de Genlis, Sophie Cottin, and George Sand, and the literary output of nine exceptionally well-read Russians, including Pushkin, Evgenia Tur, Nadezhda Khvoshchinskaya, Turgenev, Dostoevsky, and Tolstoy. Readers' tastes show that sentimentalism's debate over virtue proved tenacious because, contrary to stereotypes of the predictable triumph of good over evil, sentimentalism was an opportunistic chameleon that allowed writers to both challenge and reaffirm the social order. Responsible for Russia's empire, writers questioned whether cultivating social duties could restrain violence in a revolutionary epoch."
European and Russian Sentimentalism -- Novels and Readers -- Karamzin Translates the Comtesse de Genlis -- Education in Translation: Zhukovsky, Elagina, and Zontag -- Maria Fedorovna and Her Institutes for Noblewomen -- Pushkin and Sophie Cottin's "Mediocre" Novel -- George Sand in Russia: Tur, Turgenev, and Goncharov -- In Defence of Duty: Khvoshchinskaia and Dostoevsky -- Tolstaya vs. Tolstoy.
Includes bibliographical references and index.
ENH
Keywords: Russian fiction -- 19th century -- European influences; Russian fiction -- 19th century -- History and criticism; European literature -- Appreciation -- Russia -- History -- 19th century; European literature -- 19th century -- Translations into Russian; Best sellers -- Europe -- History -- 19th century; Comparative literature -- Russian and European; Sentimentalism in literature; Realism in literature